Feasibility of closed-MLC tracking using high sensitivity and multi-layer electronic portal imagers. (6th December 2018) - Hu, Yue-Houng; Jacobson, Matthew W; Shi, Mengying; Myronakis, Marios; Wang, Adam; Baturin, Paul; Huber, Pascal; Fueglistaller, Rony; Morf, Daniel; Star-Lack, Josh; Berbeco, Ross I
Abstract: In radiation therapy, improvements in treatment conformality are often limited by movement of target tissue. To better treat the target, tumor tracking strategies involving beam's-eye-view (BEV) have been explored. However, localization surrogates like implanted fiducial markers may sometimes leave the field-of-view (FOV), as defined by the linear accelerator (LINAC) multi-leaf collimator (MLC). Radiation leakage through the MLC has been measured previously at approximately 1%–2%. High sensitivity prototype detectors imagers may improve the ability to visualize objects outside of the MLC FOV during treatment. The present study presents a proof-of-concept for tracking fiducial markers outside the MLC FOV by employing high sensitivity detectors using a high-efficiency, prototype scintillating glass called LKH-5 and also investigates the impact of multi-layer imager (MLI) architecture. It was found that by improving the detector efficiency, using either of these methods results in a reduction of dose required for fiducial marker visibility. Further, image correction by a rectangular median filter will improve fiducial marker representation in the MLC blocked images. Quantified by measuring the peak-to-sidelobe ratio (PSR) of the normalized cross correlation (NCC) between a template of the fiducial marker with the blocked MLC acquisition, visibility has been found at a threshold of roughly 5 for all configurations with a 3 × 3 cm 2 ROI. For typical gadolinium oxysulfide (GOS) detectors in single and simulated 4-layer configurations, the minimum dose required for visualization was 20 and 10 MU, respectively. For LKH-5 detectors in single and simulated 4-layer configurations, this minimum dose was reduced to 4 and 2 MU, respectively. With a 6 MV flattening filter free (FFF) beam dose rate of 1400 MU min −1, the maximum detector frame rate while maintaining fiducial visibility is approximately 12 fps for a 4-layer LKH-5 configuration.